A Review of Iran’s Manufacturing Structure in Political Documents - Afsaneh Shafiee (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This paper aims to formulate necessary policy instruments which strengthen Iran’s manufacturing activities. In this regard, a comprehensive survey was conducted to identify challenges ahead of manufacturing production and export in Iran using meta-analysis. The results showed that there are 6 major challenges on the way of promoting manufacturing competitiveness in Iran including: increased import dependency of manufacturing production, decreasing resource (energy as well as mineral) advantages on export competitiveness, decreasing contribution of human resources on export competitiveness, decreasing reliance of manufacturing production and export on R&D as well as innovation. In this regard, there are 5 strategic policies suggested as the starting point of industrial restructuring: competition intensification, providing infrastructures supporting manufacturing production and export, making factor market more flexible, promoting added value creation capabilities, as well as provoking demand in both domestic as well export markets.